Nonlinear internal wave - topographic interaction and turbulent mixing using numerical simulations - Klema, Matthew Roy, author; Venayagamoorthy, Subhas Karan, advisor; Nelson, Peter, committee member; Rathburn, Sara, committee member; Thornton, Christopher, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: ocean mixing; turbulence; stratified turbulence; computational fluid dynamics